Post-apocalyptic stress disorder in "The Leftovers" - Front, Sonia (Adam Mickiewicz University, 2021)
In Tom Perrotta’s novel, The Leftovers (2011), and the TV series (2014–2017) based on the novel, 2% (140 million) of the world’s population vanish into thin air. The event constitutes a temporal rift that divides history into Before and After and inaugurates a new mode of temporality, marked by a break with a clock-time-based economy and a yearning for the ultimate end. This new mode of temporality is accompanied by the shattering of the individual sense of being-in-time. The essay focuses on the altered experience of time both on individual and collective levels, a condition that constitutes a kind of post-apocalyptic stress disorder. The characters’ reactions to the traumatic experience demonstrate that the inexplicability of the apocalyptic event and duration without closure are psychologically intolerable. As closure is impossible, they cannot work through the trauma, remaining trapped in the past event and the present anticipation of the ultimate annihilation while the future horizon becomes obliterated.
Keywords: The Leftovers; trauma; trauma and temporality; apocalypse; acting out; working through